1997
DOI: 10.1021/jp9700591
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical Study of Intermolecular Interaction at the Lipid−Water Interface. 1. Quantum Chemical Analysis Using a Reaction Field Theory

Abstract: Reaction field calculation combined with the AM1 molecular orbital method is applied in order to understand why intermolecular hydrogen bonding is stabilized at the lipid−water interface. Here, we focus on the interaction between a guanidinium-functionalized lipid (1) and phosphate and between a diaminotriazine-functionalized lipid (2) and thymine. The interface is approximated by a double layer composed of two dielectrics. The lower dielectric medium with a dielectric constant of 2 corresponds to the lipid la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
61
0

Year Published

1998
1998
2023
2023

Publication Types

Select...
6
4

Relationship

5
5

Authors

Journals

citations
Cited by 115 publications
(62 citation statements)
references
References 35 publications
1
61
0
Order By: Relevance
“…The magnitude of binding constants should be related to the type of interface. Sakurai and coworkers proposed application of a quantum chemical calculation to molecular recognition at the air-water interface [655][656][657]. Calculations were performed based on a multi-dielectric model for the guanidinium-phosphate system situated at an interface.…”
Section: Langmuir-blodgett Filmsmentioning
confidence: 99%
“…The magnitude of binding constants should be related to the type of interface. Sakurai and coworkers proposed application of a quantum chemical calculation to molecular recognition at the air-water interface [655][656][657]. Calculations were performed based on a multi-dielectric model for the guanidinium-phosphate system situated at an interface.…”
Section: Langmuir-blodgett Filmsmentioning
confidence: 99%
“…In particular, molecular recognition through hydrogen bonding occurs efficiently at this interface, as demonstrated in molecular recognition of bio-related substances such as peptides [149][150][151][152], nucleotidic compounds [153][154][155], and sugars [156,157] or as simulated in theoretical calculations [158][159][160]. Therefore, molecular-level patterns can be designed and prepared through molecular interaction between monolayer components and aqueous template molecules.…”
Section: Structure Formation At Dynamic Surfacementioning
confidence: 99%
“…Most importantly they found that molecular recognition at the air-water interface generally occurs with enhanced binding constants relative to those in bulk media [7]. This was also theoretically interpreted using quantum chemical calculations [8,9]. Unfortunately, chiral discrimination was not seriously discussed in Kunitake's reports although they demonstrated recognition of guest substances with chiral structures, such as sugars [10], nucleotides [11], amino acids [12], and peptides [13][14][15][16].…”
Section: Introductionmentioning
confidence: 98%